An a posteriori analysis of C0 interior penalty methods for the obstacle problem of clamped Kirchhoff plates - Brenner, Susanne C.; Gedicke, Joscha; Sung, Li-Yeng; Zhang, Yi (SIAM journal on numerical analysis, 2017)
We develop an a posteriori analysis of C0 interior penalty methods for the displacement obstacle problem of clamped Kirchhoff plates. We show that a residual based error estimator originally designed for $C^0$ interior penalty methods for the boundary value problem of clamped Kirchhoff plates can also be used for the obstacle problem. We obtain reliability and efficiency estimates for the error estimator and introduce an adaptive algorithm based on this error estimator. Numerical results indicate that the performance of the adaptive algorithm is optimal for both quadratic and cubic C0 interior penalty methods.
Im Titel ist die Zahl "0" hochgestellt
Gesehen am 23.11.2020